Vibrator and PI4KIIIα govern neuroblast polarity by anchoring non-muscle myosin II - Koe, Chwee Tat; Tan, Ye Sing; Lönnfors, Max; Hur, Seong Kwon; Low, Christine Siok Lan; Zhang, Yingjie; Kanchanawong, Pakorn; Bankaitis, Vytas A; Wang, Hongyan (eLife, 2018)
A central feature of most stem cells is the ability to self-renew and undergo differentiation via asymmetric division. However, during asymmetric division the role of phosphatidylinositol (PI) lipids and their regulators is not well established. Here, we show that the sole type I PI transfer protein, Vibrator, controls asymmetric division of Drosophilaneural stem cells (NSCs) by physically anchoring myosin II regulatory light chain, Sqh, to the NSC cortex. Depletion of vib or disruption of its lipid binding and transfer activities disrupts NSC polarity. We propose that Vib stimulates PI4KIIIα to promote synthesis of a plasma membrane pool of phosphatidylinositol 4-phosphate [PI(4)P] that, in turn, binds and anchors myosin to the NSC cortex. Remarkably, Sqh also binds to PI(4)P in vitro and both Vib and Sqh mediate plasma membrane localization of PI(4)P in NSCs. Thus, reciprocal regulation between Myosin and PI(4)P likely governs asymmetric division of NSCs. Stem cells are cells that can both make copies of themselves and make new cells of various types. They can either divide symmetrically to produce two identical new cells, or they can divide asymmetrically to produce two different cells. Asymmetric division happens because the two new cells contain different molecules. Stem cells drive asymmetric division by moving key molecules to one end of the cell before they divide. Asymmetric division is key to how neural stem cells produce new brain cells. Many studies have used the developing brain of the fruit fly Drosophila melanogaster to understand this process. Errors in asymmetric division can lead to too many stem cells or not enough brain cells. This can contribute to brain tumors and other neurological disorders. Fat molecules called phosphatidylinositol lipids are some of chemicals that cause asymmetry in neural stem cells. Yet, it is not clear how these lipid molecules affect cell behavior to turn stem cells into brain cells. The production of phosphatidylinositol lipids involves proteins called Vibrator and PI4KIIIα. Koe et al. examined the role of these two proteins in asymmetric cell division of neural stem cells in fruit flies. The results show that Vibrator activates PI4KIIIα, which leads to high levels of a phosphatidylinositol lipid called PI(4)P within the cell. These lipids act as an anchor for a group of proteins called myosin, part of the machinery that physically divides the cell. Hence, myosin and phosphatidylinositol lipids together control asymmetric division of neural stem cells. Further experiments used mouse proteins to compensate for defects in the equivalent fly proteins. The results suggest that the same mechanisms are likely to hold true in mammalian brains, although this still needs to be proven. Nevertheless, given that human equivalents of Vibrator and PI4KIIIα are associated with neurodegenerative disorders, schizophrenia or cancers, these new findings are likely to help scientists better to understand several human diseases.